HUBUNGAN ANTARA PEMBERDAYAAN PSIKOLOGIS DAN KOMITMEN KARIER PADA GURU SMA SWASTA UMUM BINAAN DISDIKPORA KOTA SALATIGA - Dwi Setya Ariani; Sutarto Wijono; Adi Setiawan (PSIKODIMENSIA, 2016)
The purpose of this research is to verify the correlation between Psychological Empowerment and Career Commitment. There are two scales used in this research, i.e. Psychological Empowerment Scales by Spreitzer (1995) and Career Commitment Scale by Carson & Bedeian (1994). The participants of this research are 60 teachers of private high-school in Salatiga, Indonesia. Data analysis uses SPSS 16 Program. Statistics method to be used is pearson product moment correlation test. The result of statistic test shows that there is significant correlation between Psychological Empowerment and Career Commitment.